2017
DOI: 10.1016/j.envint.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical exposures in recently renovated low-income housing: Influence of building materials and occupant activities

Abstract: Health disparities in low-income communities may be linked to residential exposures to chemicals infiltrating from the outdoors and characteristics of and sources in the home. Indoor sources comprise those introduced by the occupant as well as releases from building materials. To examine the impact of renovation on indoor pollutants levels and to classify chemicals by predominant indoor sources, we collected indoor air and surface wipes from newly renovated "green" low-income housing units in Boston before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…5,6 In 2017, a prospective cohort study of 3103 mother-neonate pairs found that cumulative exposures to combined phthalates (diethyl phthalate (DEP), dibutyl phthalate (DBP), dibenzyl phthalate (BBzP), and di(2-ethylhexyl) phthalate (DEHP)) were associated with a 33.1 g decrease in girls' birthweights. 13 Household renovation in the year before pregnancy and during pregnancy might also be associated with noise pollution and psychosocial stress around conception and pregnancy, which may have adverse effects on birth outcomes. 9,10 A field study of 30 newly renovated residences in Boston, USA, found that building materials for renovation expose occupants to dibutyl phthalate and xylene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 In 2017, a prospective cohort study of 3103 mother-neonate pairs found that cumulative exposures to combined phthalates (diethyl phthalate (DEP), dibutyl phthalate (DBP), dibenzyl phthalate (BBzP), and di(2-ethylhexyl) phthalate (DEHP)) were associated with a 33.1 g decrease in girls' birthweights. 13 Household renovation in the year before pregnancy and during pregnancy might also be associated with noise pollution and psychosocial stress around conception and pregnancy, which may have adverse effects on birth outcomes. 9,10 A field study of 30 newly renovated residences in Boston, USA, found that building materials for renovation expose occupants to dibutyl phthalate and xylene.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 A field study of 30 newly renovated residences in Boston, USA, found that building materials for renovation expose occupants to dibutyl phthalate and xylene. 13 Household renovation in the year before pregnancy and during pregnancy might also be associated with noise pollution and psychosocial stress around conception and pregnancy, which may have adverse effects on birth outcomes. 1,14,15 Therefore, we hypothesized that household renovation during pregnancy would have significant associations with adverse birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Health assessments were associated with moves from conventional to new green homes. (Critchley, Gilbertson et al 2007) Examines why homes remain cold, based on diaries of recorded temperatures, even after EE and heating interventions, does not focus on how EE affects health, the association with temperatures in the diaries with comfort and health are included in Gilbertson et al 2012 Study does not separate effects of EE measures from other home improvement measures (Crump, Macmillan et al 2009) Review article Review article (Dedman, Gunnell et al 2001) Study does not address EE retrofits (Dodson, Udesky et al 2017) Provides data on concentrations of volatile organic compounds after renovations, does not indicate how EE renovations affected levels. (El Ansari and El-Silimy 2008) Study of how improving warmth affected excess winter deaths, and our review is not including death as an outcome (Free, Howden-Chapman et al 2010) Study of whether improved and non-polluting home heating is associated with reduced school absences; not a study f benefits of EE (Giancola, Soutullo et al 2014) Data obtained from only two apartments (Gibson, Petticrew et al 2011) Synthesis of reviews, not focused on EE (Hopton and Hunt 1996) Assessed whether improved home heating to reduce dampness improved health, not a study of EE retrofits (Howden- Chapman, Viggers et al 2009) Review of two prior studies by same research group (Garland, Steenburgh et al 2013) Study involves moving into new homes, studies with moves excluded from our review (Green, Ormandy et al 2005) Not a journal article (Hamilton, Davies et al 2011) Modeled influence of EE interventions on indoor cold temperatures and associated health effects, provides no new empirical data (Hamilton, Milner et al 2015) Modeled effects of EE retrofits in England, provides no new empirical data (Harrington, Heyman et al 2005) This study used survey data to examine attitudes about fuel poverty and warmth, but provides no empirical data on effects of EE retrofits (Heyman, Harrington et al 2005) While paper provides data relating home energy efficiency rating with health, it does not provide data on effects of EE retrofits retrofitted building and one unoccupied apartment from the non-retrofitted building.…”
Section: Study Type Category Study Features* Randomized Controlled Trialmentioning
confidence: 99%
“…The Green Housing Study (GHS)-a project of the Centers for Disease Control and Prevention and Department of Housing and Urban Development-is evaluating the effects of "green" housing on indoor environmental quality and children's respiratory health. The study sites are in Boston, Massachusetts, Cincinnati, Ohio, and New Orleans, Louisiana (Coombs et al 2016;Dodson et al 2017). Indoor air samples were collected from households with children ages 7-12 with physician-diagnosed asthma living in subsidized housing in Boston (n = 44) and Cincinnati (n = 33) in 2012-2013.…”
Section: Unsupervised Clustering Of Environmental Chemical Measurementsmentioning
confidence: 99%